How do bipolar disease states affect positive and negative emotion processing? Insights from a meta‐analysis on the neural fingerprints of emotional processing - Förster, Katharina; Maliske, Lara Z.; Schurz, Matthias; Henneberg, Paula M.; Dannlowski, Udo; Kanske, Philipp (Bipolar disorders, 2023)
Background Functional magnetic resonance imaging studies on emotion processing in patients with bipolar disorder (BD) show hyperactivity of limbic‐striatal brain areas and hypoactivity in inferior frontal areas compared to healthy participants. However, heterogeneous results in patients with different disease states and different valences of emotional stimuli have been identified. Methods To integrate previous results and elucidate the impact of disease state and stimulus valence, we conducted a systematic literature search for journal articles in the Web of Science Core Collection including MEDLINE databases and employed a coordinate‐based‐meta‐analysis of functional‐MRI studies comparing emotion processing in BD‐patients with healthy participants using seed‐based d mapping (SDM) to test for between‐subjects‐effects. We included 31 studies published before 11/2022 with a total of N = 766 BD‐patients and N = 836 controls. Results Patients with BD showed hyperactivated regions involved in salience processing of emotional stimuli (e.g., the bilateral insula) and hypoactivation of regions associated with emotion regulation (e.g., inferior frontal gyrus) during emotion processing, compared to healthy participants. A more detailed descriptive analysis revealed a hypoactive (anterior) insula in manic BD‐patients specifically for negative in comparison to positive emotion processing. Discussion This meta‐analysis corroborates the overall tenor of existing literature that patients with BD show an increased emotional reactivity (hyperactivity of salience‐processing regions) together with a lower (cognitive) control (hypoactivity of brain areas associated with emotion regulation) over emotional states. Our analysis suggests reduced interoceptive processing of negative stimuli in mania, pointing out the need for longitudinal within‐subject analyses of emotion processing.